PENGARUH METODE MIND MAPPING TERHADAP STRATEGI THINKING ALOUD PAIR PROBLEM SOLVING TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS - Evi Lestari Rahayu; Padillah Akbar; Muhammad Afrilianto (Departement of Mathematics Education, 2019)
This research is based of low mathematics creative thinking ability from students in Vocassional High School in order to be needed study method to solve that problem. Alternatife of study method and strategy is use Mind Mapping method by Thinking Aloud Pair Problem Solving (TAPPS) strategy. The purpose of this research is to identify weather achievement of mathematics creative thinking ability of students in High School through use Mind Mapping method by Thinking Aloud Pair Problem Solving (TAPPS) strategy is better than use convensional study. The population in this study were vocational high school students in Bandung, while the sample was SMK MAARIF Cicalengka and selected two classes randomly from all of the existing XI class. Then from the two classes are assigned randomly into the experimental class and control class. The experimental class received learning get Mind Mapping Method by Thinking Aloud Pair Problem Solving (TAPPS) strategy and control class gained regular learning. The instrument used is the test of creative thinking ability mathematically. Based of the calculation and hypothesis test concluded that the achievement of creative thinking ability of mathematic of students who get Mind Mapping Method with Thinking Aloud Pair Problem Solving (TAPPS) Strategy is better than those who get regular learning.